Annual report 2019: CGIAR Research Program on Water, Land and Ecosystems - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2020)
Results from the CGIAR Research Program on Water Land and Ecosystems (WLE) demonstrate how new evidence and innovations contribute to sustainable intensification of agriculture at landscape level. WLE’s solutions support producing more nutritious food while managing natural resources more productively and sustainably in the face of critical climate change, health, demographic, and economic challenges.